2008
DOI: 10.1044/0161-1461(2008/005)
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Derived Combinations of Tools and Clinical Cutoffs: An Illustrative Case With a Sample of Culturally/Linguistically Diverse Children

Abstract: Purpose-Using a sample of culturally/linguistically diverse children, we present data to illustrate the value of empirically derived combinations of tools and cutoffs for determining eligibility in child language impairment.Method-Data were from 95 4-and 6-year-olds (40 African American, 55 White; 18 with language impairment, 77 without) who lived in the rural South; they involved primarily scores from the Comprehension subtest of the Stanford-Binet Intelligence Scale-Fourth Edition (CSSB; R. Thorndike, E. Hag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The most common metrics for describing a test's caseby-case agreement with the reference standard are sensitivity and specificity (Dollaghan & Horner, 2011;Oetting, Cleveland, & Cope, 2008;Plante & Vance, 1994). In comparing outcomes of the new test to the reference provided by the gold standard, one asks whether the new assessment will be sensitive enough to pick out all of the children in the sample the gold standard labels as having LI but also specific enough to avoid false positives-that is, children who are identified by the test as having LI but are TD according to the gold standard.…”
Section: Standard Diagnostic Accuracy Measuresmentioning
confidence: 99%
“…The most common metrics for describing a test's caseby-case agreement with the reference standard are sensitivity and specificity (Dollaghan & Horner, 2011;Oetting, Cleveland, & Cope, 2008;Plante & Vance, 1994). In comparing outcomes of the new test to the reference provided by the gold standard, one asks whether the new assessment will be sensitive enough to pick out all of the children in the sample the gold standard labels as having LI but also specific enough to avoid false positives-that is, children who are identified by the test as having LI but are TD according to the gold standard.…”
Section: Standard Diagnostic Accuracy Measuresmentioning
confidence: 99%
“…Recently, Redmond et al, (2011) showed both sensitivity and specificity above 90% in distinguishing seven-year-old children with and without language impairment. However, some studies report acceptable values for specificity but not for sensitivity both in preschool children (Conti-Ramsden, 2003; Conti-Ramsden & Hesketh, 2003), and in six- and seven-year-old children (Conti-Ramsden et al, 2001; Oetting & Cleveland, 2006; Oetting et al, 2008). Archibald and Joanisse (2009) reported relatively low values (below 70%) for both sensitivity and specificity in school-age children.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results of this study, together with those of Jacobson and Schwartz (2005) and Paradis (2008), indicate that further investigation into past tense as a clinical marker in L2 English would be worthwhile. We recommend that past tense use in particular be investigated in combination with other measures as, ultimately, combinations of measures may be needed to identify children with LI (Oetting, Cleveland, & Cope, 2008).…”
Section: Past Tense Marking In English L2 Childrenmentioning
confidence: 99%